Affordability of Islamic microfinance - Mohammad, Mohammad Tahir Sabit; Juanil, David Martin @ Daud; Eni, Sabariah (Universiti Tun Hussein Onn Maaysia (UTHM), 2018)
The affordability of the microfinance, Islamic and conventional, is questionable. The review of empirical studies thus far shows that the majority of them are expensive and only some of them are cheap and successful. Only those, which have less cost, can afford to make microfinance cheap and hence not only affordable but also have the prospect of assisting the poor, effectively releasing them from their cycle of poverty. To make an Islamic microfinance programme cheaper, alternatives are found in the literature, and the manner in which the costs of Islamic microfinance schemes through offer of sustained grants and subsidy for the cost of capital and operational costs is proposed. Zakat and sadaqah funds are proposed for grants and subsidy while awqaf funds are proposed for loans and investment in microenterprises.